Effects of dietary intervention on diabetic nephropathy: an umbrella review of systematic reviews and meta-analyses of randomized controlled trials - Cai, Linli; Huang, Yin; Li, Xingyuan; Cao, Dehong; Liu, Fang (Frontiers in Endocrinology, 2024)
Objective: To evaluate the quality of evidence, potential biases, and validity of all available studies on dietary intervention and diabetic nephropathy (DN).We conducted an umbrella review of existing meta-analyses of randomized controlled trials (RCTs) that focused on the effects of dietary intervention on DN incidence. The literature was searched via PubMed, Embase, Web of Science, and the Cochrane Database of Systematic Reviews. According to the Grading of Recommendations, Assessment, Development and Evaluation (GRADE), evidence of each outcome was evaluated and graded as "high", "moderate", "low" or "very low" quality to draw conclusions. Additionally, we classified evidence of outcomes into 4 categories.: We identified 36 meta-analyses of RCTs and 55 clinical outcomes of DN from 395 unique articles. Moderate-quality evidence suggested that probiotic supplementation could significantly improve blood urea nitrogen (BUN), total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels in DN patients. Low-quality evidence indicated that probiotic supplementation significantly improved the serum creatinine concentration, urinary albumin-creatinine ratio (UACR), fasting blood glucose (FBG), HbA1c and high-density lipoprotein cholesterol (HDL-C) in DN patients. In addition, low-quality evidence suggested that a salt restriction diet could significantly improve the creatinine clearance rate (CrCl) in patients with DN. Lowquality evidence suggested that vitamin D supplementation could significantly improve the UACR in patients with DN. In addition, low-quality evidence has indicated that soy isoflavone supplementation could significantly improve BUN, FBG, total cholesterol (TC), triglyceride (TG) and LDL-C levels in patients with DN. Furthermore, lowquality evidence suggested that coenzyme Q10 supplementation could significantly improve HbA1c, TC and HDL-C in patients with DN, and dietary polyphenols also significantly improved HbA1c in patients with DN. Finally, low-quality evidence suggested that supplementation with antioxidant vitamins could significantly improve the serum creatinine concentration, systolic blood pressure, and HbA1c level in patients with DN. Given the small sample size, all significantly associated outcomes were evaluated as class IV evidence. Conclusions: Moderate to low amounts of evidence suggest that supplementation with probiotics, vitamin D, soy isoflavones, coenzyme Q10, dietary polyphenols, antioxidant vitamins, or salt-restricted diets may significantly improve clinical outcomes in patients with DN.